2004
DOI: 10.1364/ao.43.000688
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of spiral phase plates for optical wavelengths

Abstract: We describe the fabrication and characterization of a high-quality spiral phase plate as a device to generate optical vortices of low (3-5) specified charge at visible wavelengths. The manufacturing process is based on a molding technique and allows for the production of high-precision, smooth spiral phase plates as well as for their replication. An attractive feature of this process is that it permits the fabrication of nominally identical spiral phase plates made from different materials and thus yielding di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
162
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(169 citation statements)
references
References 23 publications
2
162
0
Order By: Relevance
“…Each element of this fractional basis can be written as an ℓ and α dependent superposition of an infinite number of LG l p states, extending over both l and p. Because this superposition changes when we reorient the SPP, we explore an infinite-dimensional subspace of the full, (spatial) Hilbert space by systematically varying α (at constant step index ℓ). We stress that the contribution of LG l p modes with p = 0 to this superposition is significant; this is caused by the fact that the dislocation imprinted by the SPP on the incident field has a mixed screw-edge character [8].…”
mentioning
confidence: 94%
“…Each element of this fractional basis can be written as an ℓ and α dependent superposition of an infinite number of LG l p states, extending over both l and p. Because this superposition changes when we reorient the SPP, we explore an infinite-dimensional subspace of the full, (spatial) Hilbert space by systematically varying α (at constant step index ℓ). We stress that the contribution of LG l p modes with p = 0 to this superposition is significant; this is caused by the fact that the dislocation imprinted by the SPP on the incident field has a mixed screw-edge character [8].…”
mentioning
confidence: 94%
“…The azimuthal structure of the input coupler is such that upon reflection from either side it removes a fixed charge 2l from the beam. The input coupler is also partially transparent and since the two sides have opposite winding it allows beams from either side to pass through with no change to their charge -an effect that has been experimentally observed for a Gaussian beam [23]. The perfectly reflecting rear mirror on the other hand, is de- signed so that it adds a charge 2l to a beam.…”
mentioning
confidence: 97%
“…The optical mirrors of the vibrating cavity have been replaced by spiral phase elements which are commonly used to modify the azimuthal structure of laser beams either via reflection or transmission [23]. Given the wavelength of radiation being used they can be designed to impart a fixed topological charge to an incident beam.…”
mentioning
confidence: 99%
“…Allen et al (1992) showed that a HermiteGaussian laser beam (zero OAM) can be transformed into a Laguerre-Gaussian beam (non-zero OAM) using a pair of cylindrical lenses. Subsequently, several other methods have been developed to generate POAM in the laboratory (Oemrawsingh et al 2004;Gibson et al 2004;Gruneisen et al 2008). LaguerreGaussian beams are known as optical vortex beams because of their phase structure which is proportional to e ımφ , using the azimuthal angle, φ, and the OAM index, m. All of the photons in these optical vortex beams carry m of OAM (Harwit 2003).…”
Section: Introductionmentioning
confidence: 99%